Extraterrestrial Physics The New York debut of George Piper Dances is seen - Goldner, Nancy (Dance Books Ltd., Alton,Hampshire (UK), 2004)
The New York debut of George Piper Dances. In the best of all possible worlds, someone would make a dance for Trevitt and Nunn incorporating their puckish personalities. PALABRAS CLAVE: George Piper Dances, Michael Nunn and William Trevitt, Mesmerics, Torsion,, Steptext.